UPAYA AMERIKA SERIKAT MENGAKUISISI TIKTOK TAHUN 2020 - Ibnu Aditya Wahidin; Yuniarti (Journal Social Politica, 2023)
TikTok is a social media company from China with the largest number of users in the United States. However, TikTok is considered a threat to the dominance of US companies and the security of the privacy of its users. Therefore, the United States seeks to acquire TikTok. The objective of this study is to explain the efforts of United States of America to acquire TikTok in Trump administration era in the year of 2020. This study uses descriptive method with primary and secondary data. The data analysis technique used is qualitative. The theory used in this study is hegemony theory by Antonio Gramsci, while the concept used in this study is economic nationalism by Serdar Dinc and Isil Erel. This research explains the efforts made by the United States to acquire TikTok to maintain US hegemony in the social media sector. The efforts made by the United States can be adapted to the theory of hegemony and the concept of economic nationalism. According to Dinc and Erel in an effort to acquire a company, The United States itself fulfills at least four methods in its efforts to acquire TikTok, namely: Public Interest through the use of national security reasons which are in the public interest, Moral Persuasion through support for domestic US companies conveyed through mass media, Playing for Time through Executive Order and Presidential Documents that provide a deadline for TikTok to sell its shares to US companies, and Creating National Champion through the formation of US companies capable of acquiring TikTok. The efforts of the United States are conducted through Executive Order No. 13942, which was passed by President Trump in 2020, has practically succeeded in forcing TikTok to sell its shares to a United States company. However, the acquiring process never got underway until the change of president and President Joe Biden's repeal of the Executive Order.